REGIONAL FISCAL CAPACITY AND INVESTMENT: THE STRATEGIC IMPACT OF FOREIGN AND DOMESTIC DIRECT INVESTMENT ON LOCAL OWN-SOURCE REVENUE IN BANDUNG REGENCY - Daniel Simamora (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the short-term and long-term effects of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI) on Local Own-Source Revenue (LOR) in Bandung Regency. In the era of fiscal decentralization, the ability of local governments to increase Local Own-Source Revenue is crucial for autonomy and sustainable development. Using annual time series data from 2011 to 2024, this research applies the Autoregressive Distributed Lag (ARDL) econometric model to analyze the causal relationship between investment variables and local fiscal capacity. The primary findings indicate a cointegration relationship, or long-term equilibrium, among FDI, DDI, and LOR. The estimation results show that DDI has a positive and significant impact on Local Own-Source Revenue in both the short and long term. Conversely, FDI demonstrates a significant influence only in the long term, suggesting a lag effect from foreign investment on local revenue. A significant Error Correction Term (ECT) confirms the existence of an adjustment mechanism towards long-term equilibrium. The conclusion of this research affirms that investment, particularly from domestic sources, is a strategic determinant for strengthening the fiscal capacity of Bandung Regency, with policy implications that emphasize the importance of improving the domestic investment climate as a primary pillar of regional fiscal independence.